Causes of eye removal: Analysis of 586 eyes - Knežević Miroslav; Paović Jelena; Paović Predrag; Sredojević Vojislav (Vojnosanitetski Pregled)
Background/Aim. Eye enucleation is one of the oldest surgical procedures. The aim of the study was to determine the causes of enucleation as seen in a major reference eye center in Serbia. Methods. Retrospective case series involving a review of all enucleation procedures performed in the period between January 2000 and December 2008 at the Institute for Eye Diseases, Clinical Center of Serbia, Belgrade. The collected information included the basic demographic data and diagnosis of the affected eye. The diagnosis was made based on history, clinical and histological examinations. Clinical indications for enucleation were categorized as tumors, glaucoma, trauma, infections and other diseases. A statistical analysis was made using the Student's t-test. Results. There were 586 patients, 315 male and 271 female in our series. The mean age was 57.81, ranging from 3 months to 96 years. The most common cause of enucleations was tumor (76.11%), (p < 0.05). Choroid melanoma was the most common etiology leading to enucleation (81.18%), followed by retinoblastoma (12.34%). A total of 8.02% of enucleations were performed due to glaucoma that was primarily neovascular in 42.55% of cases or caused by trauma in 38.8% of cases. Trauma was the third common etiology of enucleation, and it was acute in 56.26% of cases or resulted in phthisis bulbi in 31.25% of cases. Enucleation caused by inflammation was performed in 2.90% of cases, out of which 52.94% of enucleations occurred after perforation of the cornea. In the group of other diseases the most common cause of enucleation was atrophy of the eye ball. Conclusion. Neoplasm, neovascular glaucoma, acute eye injury and atrophy of the eye ball are the most common causes of enucleation.